The native species of Callianthe (Malvaceae, Malvoideae) in northern South America (Colombia, Venezuela, the Guianas and adjacent Brazil) - Laurence J. Dorr (PhytoKeys)
The native species of Callianthe Donnell (Malvaceae, Malvoideae) in northern South America (Colombia, Venezuela, the Guianas and adjacent Brazil) are reviewed. Five species are recognised, of which one, C. sylvatica (Cav.) Dorr, is widespread and found not only in Colombia (Cordillera Orientale) and Venezuela (Cordillera de la Costa and Sierra Nevada de Mérida), but also Andean Ecuador, Peru and Bolivia. The other four species have more restricted geographic ranges: C. clarkei Dorr, sp. nov. is known only from the Wassarai [Wassari] Mountains of southern Guyana; C. petiolaris (Kunth) Donnell occurs only in the Cordillera Orientale of Colombia; and C. roseangelae Dorr, sp. nov. is restricted to the Sierra Nevada de Mérida of Venezuela. A dearth of wild collections hampers establishing the precise native range of C. insignis (Planch.) Dorr, comb. nov., which was discovered in the Andes of either Colombia or Venezuela and quickly entered cultivation. A Brazilian species, Sida speciosa Willd. ex Spreng. (≡ S. rosea Link & Otto), erroneously purported to occur in Venezuela, belongs in Callianthe and is recognised here as a synonym of C. purpurascens (Link) Dorr, comb. nov. Nine typifications are designated for synonyms of Callianthe species; seven are for names in Abutilon Mill. and two for names in Sida L.